2020
DOI: 10.3390/biomedicines8090365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia Preconditioned Secretomes on Lymphangiogenic and Angiogenic Sprouting: An in Vitro Analysis

Abstract: Hypoxia Preconditioned Plasma (HPP) and Serum (HPS) are two blood-derived autologous growth factor compositions that are being clinically employed as tools for promoting tissue regeneration, and have been extensively examined for their angiogenic activity. As yet, their ability to stimulate/support lymphangiogenesis remains unknown, although this is an important but often-neglected process in wound healing and tissue repair. Here we set out to characterize the potential of hypoxia preconditioned secretomes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…We have shown that the localized delivery of peripheral blood-derived hypoxia-induced growth factor-mixtures can serve as a tool for the natural promotion of spatio-temporally controlled regeneration [ 15 , 16 , 17 , 18 ]. In accordance to the principle that the host response for optimal wound healing depends on multiple regulatory pathways [ 19 , 20 ], these paracrine proteins are used to stimulate a range of targeted cellular responses including wound angiogenesis, lymphangiogenesis, matrix deposition and re-epithelialization through fibroblast migration and proliferation [ 16 , 18 , 20 , 21 , 22 , 23 , 24 , 25 ]. Previous work by our group has already shown that collagen scaffolds containing hypoxia-induced growth factor proteins, produced by dermal fibroblasts, can promote vascularization and improve deep scaffold oxygenation when implanted in vivo in a rabbit model [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that the localized delivery of peripheral blood-derived hypoxia-induced growth factor-mixtures can serve as a tool for the natural promotion of spatio-temporally controlled regeneration [ 15 , 16 , 17 , 18 ]. In accordance to the principle that the host response for optimal wound healing depends on multiple regulatory pathways [ 19 , 20 ], these paracrine proteins are used to stimulate a range of targeted cellular responses including wound angiogenesis, lymphangiogenesis, matrix deposition and re-epithelialization through fibroblast migration and proliferation [ 16 , 18 , 20 , 21 , 22 , 23 , 24 , 25 ]. Previous work by our group has already shown that collagen scaffolds containing hypoxia-induced growth factor proteins, produced by dermal fibroblasts, can promote vascularization and improve deep scaffold oxygenation when implanted in vivo in a rabbit model [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these fundamental concepts, we had previously developed a novel approach for providing a biomimetic cocktail of blood-derived growth factor proteins within a locally-deployable carrier [ 16 , 17 , 18 ]. For this purpose, the primary stimulus of the wound healing angiogenic response, i.e., hypoxia, is used to stimulate PBCs to produce ‘new’ angiogenic and lymphangiogenic protein factors [ 16 , 18 , 23 , 24 , 25 ]. To obtain these complex growth factor mixtures we utilize a method of hypoxia-adjusted in vitro preconditioning, by cultivating PBCs ex vivo within a self-regulated low-oxygen microenvironment [ 16 , 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue, we invited research and review papers in various areas of oxygen biology research that focused on the fundamental understanding of HIF signaling pathways and related gene expression profiling, as well as pharmacogenomic biomarkers, molecular targets driving the regulation of human physiology and pathophysiology, and validation in animal models. As a result, we published six original papers and three review articles in this Special Issue [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
mentioning
confidence: 99%
“…The term “secretome” is a general term that includes not only soluble proteins released from cells via the endoplasmic reticulum (ER)-Golgi pathway, but also extracellular matrix proteins and cleaved fragments of membrane proteins. Moog et al have shown that the properties of the secretome are affected by hypoxia in a series of studies [ 16 , 17 , 18 ].…”
mentioning
confidence: 99%